University radio in the andean region: Alternative means in time of covid-19 - Martínez, César Andrade; Ruiz, Abel Suing; Renó, Denis Porto [UNESP] (My University, 2021)
The research seeks to evaluate the actions of university radio during the pandemic in relation to the type of information that is disseminated on health protocols and measures, specialized programming, and citizen participation. The methodology is qualitative with an exploratory and descriptive approach, a non-probabilistic sampling was carried out for convenience and content analysis on the form of transmission of various stations on their Web platforms and social networks, in addition to the collection of data through an online survey which collects the opinion of 323 radio listeners, and semi-structured interviews with experts. The results present a medium-high index of reliability on the effectiveness of the issuers. The current situation due to Covid-19 points to university radios as the revealing and innovative means of communication that allows society to participate with the freedom to share and receive timely, truthful and reliable information that helps save lives.
Radio universitaria en la región andina: Medio alternativo en tiempos de covid-19
Keywords: Covid-19; Participation; Security; University radio